The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/eji.200323715
|View full text |Cite
|
Sign up to set email alerts
|

Virus infection expands a biased subset of T cells that bind tetrameric class I peptide complexes

Abstract: We have used a TCR g -chain transgenic mouse to examine the relationship between the ability of a T cell to bind soluble class I-peptide complexes and its response to antigenic stimulation in vivo. T cells from gBT-I.3 g TCR g -chain transgenic mice preferentially carried TCR § -chains bearing the same V § 2 V region as found in the parent receptor specific for an immunodominant HSV-1 gB-peptide. Furthermore, CD8 + T cells from these mice bound K bgB tetrameric complexes with relatively high frequency, and mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In some cases, even following infection, a subset of the epitope-specific naïve pool remains unrecruited (Coles et al, 2003;La Gruta et al, 2010;Malherbe et al, 2004;Obar et al, 2008). Moreover, direct comparison of TCR usage in naïve and immune epitopespecific T cell repertoires revealed that some T cells, whilst abundant in the naïve repertoire, are nevertheless greatly and reproducibly diminished in the immune repertoire upon viral challenge (Cukalac et al, 2015;Neller et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, even following infection, a subset of the epitope-specific naïve pool remains unrecruited (Coles et al, 2003;La Gruta et al, 2010;Malherbe et al, 2004;Obar et al, 2008). Moreover, direct comparison of TCR usage in naïve and immune epitopespecific T cell repertoires revealed that some T cells, whilst abundant in the naïve repertoire, are nevertheless greatly and reproducibly diminished in the immune repertoire upon viral challenge (Cukalac et al, 2015;Neller et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, analysis of epitope-specific TCRβ transgenic CD4 + and CD8 + T cells identified clones in the naïve repertoires that were not utilized in the immune response (Coles et al, 2003;Malherbe et al, 2004). Incomplete CTL precursor recruitment was also observed for endogenous CD8 + T cell populations following either vesicular stomatitis virus (VSV) or influenza A virus (IAV) infection of mice (La Gruta et al, 2010;Obar et al, 2008), and depletion of Treg cells prior to infection with Listeria monocytogenes resulted in the elicitation of a novel CD8 + T cell population (Pace et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…variable domains that facilitate appropriate ab heterodimer assembly (31,58,59). Alternatively, the prevalence of particular TCRab combinations could arise through enrichment of particular TCRs during the process of thymic positive selection (34,(60)(61)(62) and creating MHC-specific TCRs (37). Biased ab-chain pairing is observed in peripheral TCR repertoires from a number of singlechain TCR transgenic mice (60,63,64), suggesting that constraints on ab pairing may be a key determinant in shaping the composition of TCR repertoires.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of structural, biophysical, and functional data demonstrate that both a-and b-chains of TCRs make significant contributions to interactions with pMHC ligands and this in turn determines how both TCR chains engage pMHC for optimal recognition (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Despite the combinatorial nature of TCRab recognition, assessments of epitope-specific TCR repertoire diversity have largely focused on TCR b-chains.…”
mentioning
confidence: 99%
“…In addition to secreting IFN-␥, an important cytokine mediator of cell-mediated immunity, T cells undergo proliferation and migration and release other effector molecules that facilitate their critical function during a viral infection: clearance of virus-infected cells in vivo. Previous murine studies have utilized fluorescent syngeneic splenocytes pulsed with known T-cell epitopes to sensitively measure virus-specific elimination in vivo (1,7,12,25). No assessment of in vivo T-cell recognition and clearance of SIV/HIV-1 in nonhuman primates has previously been undertaken.…”
Section: Control Of Persistent Intracellular Pathogens Such As Human mentioning
confidence: 99%